1979
DOI: 10.1017/s000335610002300x
|View full text |Cite
|
Sign up to set email alerts
|

Pre-puberal plasma luteinizing hormone concentrations and progesterone concentrations during the oestrous cycle and early pregnancy in Galway and Fingalway female lambs

Abstract: Twenty-four young female sheep, 12 Galways and 12 Fingalways, were used to study the effects of breed and level of nutrition on prepuberal plasma luteinizing hormone and progesterone concentrations throughout the oestrous cycle and during the first 35 days of pregnancy. The sheep were spring-born and were housed at the end of July when they weighed approx. 34 kg. Equal numbers of animals from each breed were fed on a concentrate diet either ad libitum or at a restricted level that was slightly above their esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The higher mortality of lambs born to P ewes may be in part due to the observed poor mothering ability of their dams. In addition, Quirke & Gosling (1979) and Quirke (1981) reported that ewe lambs usually produce weak progeny that will not survive the postnatal life. As for diet, the sorghum groups were found to have slightly lower lamb mortality proportion and this may be attributed to the higher body weight of dams and lambs.…”
Section: Discussionmentioning
confidence: 99%
“…The higher mortality of lambs born to P ewes may be in part due to the observed poor mothering ability of their dams. In addition, Quirke & Gosling (1979) and Quirke (1981) reported that ewe lambs usually produce weak progeny that will not survive the postnatal life. As for diet, the sorghum groups were found to have slightly lower lamb mortality proportion and this may be attributed to the higher body weight of dams and lambs.…”
Section: Discussionmentioning
confidence: 99%
“…In the sheep the major long-term nutritional influences on ovulation rate are seen in the adult rather than at the pubertal oestrus (Quirke & Gosling, 1979;Hamra & Bryant, 1982), but the opposite is true in pigs. For example, in the major European pig breeds daily ME intakes of 34 MJ as opposed to 21 MJ during the rearing phase enhanced average ovulation rate by 1.5 with a further response of 1.8 when intake during the oestrous cycle was increased to 41 MJ (for review, see Aherne & Kirkwood, 1985).…”
Section: E F F E C T S O F P L a N E O F N U T R I T I O Nmentioning
confidence: 99%
“…These sheep were particularly prone to long cycle-lengths, both prior to and following mating with the fertile rams. The observations of Quirke and Gosling (1979) on plasma progesterone concentrations support both possibilities. A delay in the onset of oestrus in response to 'environmental stressors' has been reported elsewhere (Doney, Gunn and Griffiths, 1973;Doney, Gunn, Smith and Carr, 1976).…”
Section: Discussionmentioning
confidence: 56%